Vacinação e hesitação vacinal: percepções dos médicos da atenção primária à saúde - SILVA, Dyegila Karolinne Costa da (2021)
Vaccination is a prevention strategy and an investment in health. The National Immunization Program in Brazil is of great importance with the achievement of the eradication of various diseases. However, in recent years, there has been a reduction in the number of people vaccinated and, consequently, the reappearance of diseases that were considered to be eradicated. Hesitation to vaccinate – the reluctance or refusal, despite the availability of the vaccine – threatens to reverse the progress made in combating diseases that can be prevented through immunization. Objectives: To analyze the perceptions of primary care physicians in São Luís, Maranhão, about the importance of vaccines and the refusal of vaccination and describe the causes attributed to vaccine hesitation. Methodology: Cross-sectional, descriptive study, where the variables of interest were registered through a semi-structured questionnaire with open and closed questions for primary health care physicians in São Luís, Maranhão. Results: Most were women (58.5%), married or in a stable relationship (58.5%), with children (51.2%), over 35 years old (53.7%), over five years of graduation (56.1%), no specialization course (53.7%), had a vaccination card (92.7%) and received immunization against influenza (97.6%), triple viral (92.7%) and COVID 19 (75.6%). 100% of physicians considered the National Immunization Program trustworthy and have already treated patients who had doubts and/or fears about the safety and/or efficacy of vaccines. 82.9% responded that adverse events in vaccination were not frequent. 70.7% considered that vaccines are tested for both safety and efficacy before being marketed. 100% believed that vaccines protect children early before exposure to infectious diseases. 95.1% responded that not vaccinating a minor compromises herd immunization. 90.2% did not consider it ethical to respect only the patient's wishes and disregard the health of others. 58.5% responded that a school cannot refuse to receive an unvaccinated child due to the refusal to vaccinate. 85.4% considered it defensible for parents to decide on the application of vaccines to their children. 95.1% reported that doctors cannot refuse to assist families who are against vaccination. 87.8% believe they should report them for refusing to vaccinate their children. 68.3% considered the lack of knowledge about vaccines as the main factors responsible for the refusal of the vaccination process and 24.9% cited Fake News as the main causes of hesitation. Conclusion: The study concluded that the National Immunization Program is considered trustworthy by physicians. Health professionals assist patients who have doubts and/or fears about the safety and/or efficacy of vacines. Doctors do not consider the adverse effects of vaccination frequent and trust that vaccines are tested for efficacy and safety. The lack of knowledge and the dissemination of Fake News are the main causes of vaccine hesitation. Final considerations: Investments should be made in the structuring of primary health care services to face vaccine refusal. The need to organize coping programs is highlighted so that professionals can correctly guide their patients about the efficacy and safety of vaccines, fighting the Fake News and other causes of vaccine refusal.